Assessing the impact of the 2008 health reform in Ecuador on the performance of primary health care services: an interrupted time series analysis - Sergio E Flores Jimenez; Miguel San Sebastián (BMC, 2021)
Abstract Background In 2008, Ecuador started a national health reform based on the principles of Alma Ata to achieve Universal Health Coverage. While coverage indicators have increased, a systematic assessment of the impact of the reform on the delivery of health services at primary level is lacking. The aim of this study was to assess the impact of the 2008 health reform on the performance of primary health care services in Ecuador. Methods Ambulatory Care Sensitive Conditions (ACSC) are a subset of diseases where hospital admission is potentially avoidable by high quality well-functioning primary care. Thus, observing the behaviour of ACSC hospitalizations can serve as an indicator of how the primary health care level is performing. Crude and adjusted rates, stratified by sex, were calculated from ten selected ACSC hospitalization discharges during 22 years of data representing 11 years before and after the health reform. An interrupted time series analysis was then conducted by applying a negative binomial regression and adjusting for overdispersion and autocorrelation. Results Overall higher crude and adjusted rates for ACSC hospitalizations were observed in women compared to men; both increased gradually since the start of the observation, reaching a peak around 2010, and then started a downwards trend. In men, the incidence rate ratio increased significantly by 3 % per year during the period before the intervention. During the first year after intervention, an increase (13 %) was detected, and then a statistically significant 1 % decrease (IRR = 0.99; 95 % CI: 0.98, 0.99) was observed in the ACSC rate ratio per year in the period after the intervention. Similar trends and effect sizes were found for women. Conclusions The study revealed significant decreasing trends of the ACSC hospitalization rates in both sexes, indicating an improvement of the performance of the primary health care services following the 2008 national health reform. A continuous strengthening of the primary care model as well as a regular monitoring of ACSC hospitalization rates in the country is recommended. A health economic evaluation considering hospitalizations avoided and associated costs is also advisable.